UNDERSTANDING AND ENHANCING ICT IN SCHOOL EDUCATION - Nanda, Chinmayee (International Journal of Psychosocial Rehabilitation, 2020)
Information and communication technology (ICT) today has pervaded almost every sphere of human life, and looks set to conquer a whole new frontier, the education field. ICT act as a perfect motivating tool. ICT as a more comprehensive umbrella that implies convergence and hybridization of technology is a recent development in Indian education. The students can receive a high-quality education through Information and communication technology by providing teachers with high-quality professional development and support.Children’s early experiences with ICT and other media will impact on their development, and their experiences of childhood. It supports children’s cognitive and emotional development and the development of social and co-operative skills. So now a strong focus should be needed on the development of ICT policy, and interaction of ICT in curriculum and practice across the whole education sector. This will lead to enable the future generation to have access to the skills for coping with and the ability to function effectively in this age of information and knowledge. The ICT unit would have the responsibility of implementing the goals and objectives of the national educational strategic and Action plan. Moreover, I consider that the use of ICT development reflection, collaboration and autonomy amongst learners which also would lead to quality in education and continuous self-development. The purpose of this paper is to know the use of ICT in various school education of India, national goal for ICT and integration of ICT in School Education.